The Mediating Role of Critical Reading Self-Efficacy Perception in the Effect of Philosophy of Education Dispositions on Curriculum Literacy - Onur Er; Özden Demir (SAGE Open)
The study used a correlational design based on a cause-and-effect relationship among philosophy of education dispositions, critical reading self-efficacy perceptions, and curriculum literacy perceptions. Five theoretical models were proposed in light of the theories and research explaining the relationships between the variables. In addition, structural equation modeling was established to determine whether a significant difference existed between the mediator variable critical reading self-efficacy perception, predictor variable, and outcome variable. SPSS PROCESS macro, Model 4 (Version 4.1; Hayes, 2022) was used for mediation analysis. The study was conducted with 158 prospective Turkish language teachers determined by the non-probability cluster sampling method in Turkey in the fall semester of the 2023 to 2024 academic year. Path analysis was performed to determine the significance of the hypotheses. The results indicated that prospective teachers’ philosophy of education dispositions and curriculum literacy perceptions affect each other positively, and critical reading self-efficacy perceptions and curriculum literacy perceptions affect each other positively. It was concluded that critical reading self-efficacy perception had a high mediating role in the effect of philosophy of education dispositions on curriculum literacy.